Co-Presence and Contingency: Comics as a Methodological Innovation in Researching Automated Futures. (September 2022) - Dahlgren, Kari; Pink, Sarah; Strengers, Yolande; Nicholls, Larissa
Recent interest in futures anthropology has argued that the discipline should play a more active role in shaping futures. However, this raises methodological problems for accessing futures and recreating the co-presence that is central to ethnography. Studying automated futures is particularly challenging because of the strong visions of technology-led futures, which rely on solutionist narratives and fail to account for everyday life. This article discusses a methodological innovation for studying automated futures through ethnographic visits, home tours, and comic strips that enable imaginative potential while drawing in the realities of everyday life and the maintenance of contingency into the future.